Dislocation/hydrogen interaction mechanisms in hydrided nanocrystalline palladium films. (1st June 2016) - Amin-Ahmadi, Behnam; Connétable, Damien; Fivel, Marc; Tanguy, Döme; Delmelle, Renaud; Turner, Stuart; Malet, Loic; Godet, Stephane; Pardoen, Thomas; Proost, Joris; Schryvers, Dominique; Idrissi, Hosni
Abstract: The nanoscale plasticity mechanisms activated during hydriding cycles in sputtered nanocrystalline Pd films have been investigated ex-situ using advanced transmission electron microscopy techniques. The internal stress developing within the films during hydriding has been monitored in-situ . Results showed that in Pd films hydrided to β-phase, local plasticity was mainly controlled by dislocation activity in spite of the small grain size. Changes of the grain size distribution and the crystallographic texture have not been observed. In contrast, significant microstructural changes were not observed in Pd films hydrided to α-phase. Moreover, the effect of hydrogen loading on the nature and density of dislocations has been investigated using aberration-corrected TEM. Surprisingly, a high density of shear type stacking faults has been observed after dehydriding, indicating a significant effect of hydrogen on the nucleation energy barriers of Shockley partial dislocations. Ab-initio calculations of the effect of hydrogen on the intrinsic stable and unstable stacking fault energies of palladium confirm the experimental observations. Graphical abstract: